Optimalisasi Pelaksanaan Rehabiitasi Medis Bagi Narapidana Narkotika di Lapas Kelas II A Gorontalo - Abdul Razak Suleman; Marwan Marwan; Sumiyati B (Jurnal Litigasi Amsir, 2025)
Medical rehabilitation is one of the key programs for inmates convicted of narcotics offenses at Class II A Gorontalo Prison, in line with the Decree of the Director General of Corrections Number: PAS-36.OT.02.02 of 2020. This study examines the factors inhibiting optimal medical and social rehabilitation for drug inmates and outlines the stages of the prison’s medical rehabilitation program. Using normative and empirical legal methods, the study finds that obstacles include limited medical facilities, inadequate infrastructure, the presence of inmates with serious illnesses, and lack of family support. The Therapeutic Community (TC) rehabilitation program consists of four stages: Detox, Induction, Primary, and Re-entry. Despite these challenges, the TC program continues to run effectively, fostering discipline and reducing inmates’ dependence on drugs.